Perancangan Promosi Klinkink Apparel melalui Media Katalog - Jeffry Jofano,; M.Nasrul Kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
This design aims to help inform the products of Klinkink Apparel in an informative and communicative way. Materials for designing in the form of initial and final surveys were carried out such as interviews, documentation, and data collection to the owners of the Klinkink Apparel who were in the Painan area. The design in this catalog design uses a minimalist and modern concept and is combined with fashion photography, the result of this concept is a more attractive product photo. It is hoped that this catalog design can make good progress through promotion, on the one hand it also strengthens the selling power and popularity of competitors for clothing brands that exist today.Keywords: Klinkink apparel, catalog, promotion, design, product.